Positioning device for MRI-guided high intensity focused ultrasound system - Milonas, Nicos; Damianou, Christakis A.; Ioannides, Kleanthis (My University, 2008)
Objective: A prototype magnetic resonance imaging (MRI)- compatible positioning device was used to move an MRI-guided high intensity focused ultrasound (HIFU) transducer. The positioning device has three user-controlled degrees of freedom that allow access to various targeted lesions. Materials and methods: The positioning device was designed and fabricated using construction materials selected for compatibility with high magnetic fields and fast switching magnetic field gradients encountered inside MRI scanners. The positioning device incorporates only MRI compatible materials such as piezoelectric motors, plastic sheets, brass screws, plastic pulleys and timing belts. The HIFU/MRI system includes the multiple subsystems (a) HIFU system, (b) MR imaging, (c) Positioning device (robot) and associate drivers, (d) temperature measurement, (e) cavitation detection, (f) MRI compatible camera, and (g) Soft ware. Results: The MRI compatibility of the system was successfully demonstrated in a clinical high-field MRI scanner. The ability of the robot to accurately move the transducer thus creating discrete and overlapping lesions in biological tissue was tested successfully. Conclusion: A simple, cost effective, portable positioning device has been developed which can be used in virtually any clinical MRI scanner since it can be sited on the scanner's table. The propagation of HIFU can use either a lateral or superior-inferior approach. Discrete and large lesions were created successfully with reproducible results. © CARS 2008.
Keywords: MRI; Positioning; Robot; Ultrasound